STUDY OF RETINAL VENOUS OCCLUSIVE DISEASES AND THEIR RISK FACTORS - KARAMBELKAR, V. H.; GAVASKAR, SAYLI M.; PATIL, ANJALI D.; JOSHI, B. S.; GADRE, GIRISH; MANE, D. A. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Introduction: Retinal vein occlusions (RVOs) are the most common retinal vascular disease second to diabetic retinopathy and a major cause of vision loss. Methods: The present study was done at our tertiary care center to study the role of risk factors in Retinal Venous Occlusive diseases and correlation of occurrence of lesions with various risk factors. The study objective is to study the role of risk factors in Retinal Venous Occlusive diseases. Results: Retinal vein occlusion (RVO) is a significant cause of loss of vision. Of the two major types of RVO, Branch Retinal Vein Occlusion (BRVO) is 4-6 times more widespread than Central Retinal Vein Occlusion (CRVO) and is the most frequent type of RVO. Hyperhomocysteinemia is a significant risk factor for RVO in patients below 40 years on age. Presence of multiple risk factors increases the chances of development of RVO. Conclusion: There is a statistically significant difference between Known cases and Newly Diagnosed cases of RVOs, showing that there is a higher risk of developing RVOs in patients.